2017
DOI: 10.1038/s41598-017-17875-0
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA expression profile reveals lncRNAs signature associated with extracellular matrix degradation in kashin-beck disease

Abstract: Kashin-Beck disease (KBD) is a deformative, endemic osteochondropathy involving degeneration and necrosis of growth plates and articular cartilage. The pathogenesis of KBD is related to gene expression and regulation mechanisms, but long noncoding RNAs (lncRNAs) in KBD have not been investigated. In this study, we identified 316 up-regulated and 631 down-regulated lncRNAs (≥ 2-fold change) in KBD chondrocytes using microarray analysis, of which more than three-quarters were intergenic lncRNAs and antisense lnc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Molecular biological network can predict molecular interactions according to gene expression patterns, which reflects the relationship between gene expression and regulation . Present study showed that LncRNAs could form double strands with relevant miRNAs, which influenced the function of mRNAs by regulating miRNAs .…”
Section: Discussionmentioning
confidence: 78%
“…Molecular biological network can predict molecular interactions according to gene expression patterns, which reflects the relationship between gene expression and regulation . Present study showed that LncRNAs could form double strands with relevant miRNAs, which influenced the function of mRNAs by regulating miRNAs .…”
Section: Discussionmentioning
confidence: 78%
“…Laminins are a family of heterotrimeric ECM proteins 33 . Previous studies have shown the expressions of specific laminins were differentially regulated during development, adhesion, migration and regeneration [34][35][36] . In our study, LAMA2 was observed to be up-regulated in KBD group in comparison to OA.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of mitochondria-related genes identified nine more up-regulated genes in Kashin-Beck disease versus normal control involved in three canonical pathways of oxidative phosphorylation, apoptosis signaling and pyruvate metabolism [97]. Expression profiles in cultured chondrocytes revealed 232 up-and 427 down-regulated mRNAs and 316 up-and 631 down-regulated lncRNAs [98]. A lncRNA-mRNA correlation analysis yielded 509 coding-noncoding gene co-expression networks, and eleven lncRNAs were predicted to have cis-regulated target genes, and co-expressed mRNAs and lncRNAs formed large network associated with the biological events of extracellular matrix [98].…”
Section: Selenium-related Gene Expressions In Some Pathological Condimentioning
confidence: 99%
“…Expression profiles in cultured chondrocytes revealed 232 up-and 427 down-regulated mRNAs and 316 up-and 631 down-regulated lncRNAs [98]. A lncRNA-mRNA correlation analysis yielded 509 coding-noncoding gene co-expression networks, and eleven lncRNAs were predicted to have cis-regulated target genes, and co-expressed mRNAs and lncRNAs formed large network associated with the biological events of extracellular matrix [98].…”
Section: Selenium-related Gene Expressions In Some Pathological Condimentioning
confidence: 99%